Effects of Exercise Combined with Undenatured Type II Collagen on Endurance Capacity, Antioxidant Status, Muscle Lipogenic Genes and E3 Ubiquitin Ligases in Rats - Orhan, Cemal; Sahin, Emre; Er, Besir; Tuzcu, Mehmet; Lopes, Andrey P.; Şahin, Nurhan; Şahin, Kazım (Mdpi, 2021)
Simple Summary Undenatured type II collagen (UCII), a collagen product that modulates the immune system by oral tolerance, has become a novel alternative agent to support skeletal system health. The current study explored the impact of UCII on endurance capacity, oxidative stress, inflammation, and antioxidant defense markers in exercised rats. UCII supplementation decreased serum lactate, malondialdehyde, inflammatory marker levels (TNF-alpha) and improved antioxidant status and lipid metabolism in training rats. The current study aimed to investigate the effect of exercise combined with undenatured type II collagen (UCII) administration on endurance capacity, lipid metabolism, inflammation, and antioxidant status in rats. Twenty-one male Wistar albino rats were divided into three groups as follows: (1) Sedentary control, (2) Exercise (E), (3) Exercise + UCII (4 mg/kg BW/day; E + UCII). The findings showed that the exhaustive running time in the UCII group was significantly prolonged compared to that of the non-supplemented group (p < 0.001). When compared to the control group, total serum cholesterol (TC, p < 0.05) and triglyceride (TG, p < 0.05) levels decreased, while creatinine kinase (CK) levels increased in the E group (p < 0.001). Serum creatinine kinase levels were reduced in the E + UCII group compared to the E group (p < 0.01). Serum lactate, myoglobin (p < 0.01), and osteocalcin levels (p < 0.01) increased significantly in exercised rats compared to sedentary control rats, while serum lactate (p < 0.01) and myoglobin (p < 0.0001) levels decreased in the E + UCII group compared to control. Additionally, UCII supplementation caused significant increases in antioxidant enzyme activities [SOD (p < 0.01) and GSH-Px (p < 0.05)] and decreases in malondialdehyde (MDA) and tumor necrosis factor (TNF-alpha) levels (p < 0.001). Muscle lipogenic protein (SREBP-1c, ACLY, LXR, and FAS) levels were lower in the E + UCII group than in other groups. In addition, UCII supplementation decreased muscle MAFbx, MuRF-1, myostatin and increased MyoD levels in exercised rats. Moreover, the E + UCII group had lower muscle inflammatory markers [TNF-alpha (p < 0.0001) and IL-1 beta (p < 0.01)] than the control group. These results suggest exercise combined with UCII (4 mg/kg BW/day) modulates lipid, muscle, and antioxidant status in rats.
Keywords: exercise; endurance; undenatured type II collagen; anti-inflammatory; antioxidants; immune response